Prototype Output from Renewable Energy Power Sources and Its Application to Some Electrical Equipment Controlled Using IoT - MOHD FAUZZI, AHMAD AMIRUL AFIQ; ROSLAN, HAZLI (Progress in Engineering Application and Technology, 2022)
This research describes the combination of renewable energy, namely solar, wind and hydro energy which to overcome problems such as weather changes and prolonged cloudy weather. By using only one energy source, then the power produced is very little compared to the combined with other renewable energy. This research will combine the power obtained between solar, wind and hydro energy and the power will be stored in the battery. Problems such as prolonged rain will make the solar panel will not produce power. As a result, a prototype has been made to counter the problem which has combine all the equipment of renewable energy such as solar panels, wind turbines and mini-hydro generator motor turbines. In addition, the purpose of this study is to design a method for the remote control of electrical equipment by making use of an embedded system and having it controlled via the internet of things. Using microcontrollers and WiFi networked to mobile phones, control systems for various pieces of machinery may be manufactured. For the purpose of controlling the activation of load that is controlled by a smart phone, this research will include the usage of ESP 32 WiFi as well as a relay. The study also recorded that the power gained depends on the different types of renewable energy. Weather conditions played a very important role throughout the conduct of this study.